Engineering mathematics: for cse and it - Bhui, Bikash Chandra (Vikas Pub, 2009)
Engineering mathematics: for cse and it / Bhui, Bikash Chandra. -- Kolkata: Vikas Pub, 2009 510 B575V4 No. of Copies : 1